The global language of today (Philology, 2022)
This article is an attempt to shed light on the causes of the widespread spread of English around the world by turning it into a global language and Global English. The criteria according to which a language can be considered a global language are set out. Its status inevitably has an impact on both the population of English-speaking countries and those who study it as a foreign language.
Keywords: global language; English language; global English language